X-Linked Lymphoproliferative Syndrome and Common Variable Immunodeficiency May Not Be Differentiated by SH2D1A and XIAP/BIRC4 Genes Sequence Analysis - Nesrin Gulez; Guzide Aksu; Afig Berdeli; Neslihan Karaca; Sema Tanrıverdi; Necil Kutukculer; Elif Azarsiz (Case Reports in Medicine)
The X-linked lymphoproliferative syndrome (XLP) is a rare, inherited immunodeficiency characterized by recurrent episodes of hemophagocytic lymphohistiocytosis, hypogammaglobulinemia, and/or lymphomas. Recently, X-linked inhibitor of apoptosis (XIAP/BIRC4) gene defects, in families with XLP but without SH2D1A gene defects, has been defined. The distinction from primary immunodeficiencies with a defined genetic cause is mandatory. A six-year-old male patient was admitted with the complaints of persistent general lymphadenopathy, for two years had fever, bilateral cervical multiple microlymphadenopathy, hepatic/splenic enlargement with laboratory findings as decreased serum immunoglobulins, negative EBV VCA IgM (viral capsid antigen) and anti-EBV EA (antibody to early D antigen), positive EBV VCA IgG (viral capsid antigen) and EBV EBNA (antibody to nuclear antigen). SH2D1A gene analysis was negative. XIAP/BIRC4 sequencing revealed two novel single nucleotide variants (exon 7, 1978G > A, and 1996T > A) in the 3′UTR of the gene in both patient and mother which were not disease causing. XIAP protein expression was found to be normal. The clinical and laboratory resemblance, no gene mutations, and normal XIAP protein expression led us to think that there may be another responsible gene for XLP. The patient will to be followed up as CVID until he presents new diagnostic signs or until the identification of a new gene.